Improved Constant Switching Frequency Torque Regulator based DTC of IM Fed by 3L-NPC Inverter for Wide Speed Region - Hakami, Samer Saleh; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (CENCON 2019 - 2019 IEEE Conference on Energy Conversion, 2019)
Classical direct torque control (DTC) is popular for its simplicity and fast control algorithm in motor drives. However, it has two main weaknesses; unfixed inverter switching frequency and large torque ripples due to torque hysteresis controller (THC). In DTC drives, torque ripple can be minimized by replacing the two-level inverter with a three-level neutral-point clamped (3L-NPC) inverter. Nevertheless, switching frequency is still variable and low which produces higher torque ripple and asymmetrical switching signals for the inverter. To alleviate these problems, a conventional constant switching frequency torque regulator-based DTC (CSFTR-DTC) for 3L-NPC inverter was presented in the literature. However, the conventional CSFTR-DTC deteriorates from flux-droop at sector transitions at low speed operation. This results in undesirable speed oscillation and high total harmonic distortion (THD) of the stator current. Moreover, the torque ripple is still relatively high. In this paper, an improved interleaving CSFTR-DTC is proposed to modify the duty cycle of torque-error status in three-level inverter to improve flux-regulation and reduce torque ripples. Simulation results are presented to validate the effectiveness of the proposed method over the conventional method.
Keywords: Constant switching frequency; Conventional methods; Direct torque control; Hysteresis controller; Inverter switching frequency; Three-level inverters; Three-level neutral point clamped; Total harmonic distortion (THD); constant switching frequency torque controller; direct torque control; flux-droop; induction motor; three-level neutral-point clamped inverter